Spider silk inspired materials and sustainability: perspective. (6th June 2016) - Lefèvre, T.; Auger, M.
Abstract : Spider silk is one of the best illustrations of biomimetism. Thanks to a complex hierarchical structure, this fibre exhibits remarkable characteristics, especially renowned tensile properties. Silk filaments result from a complex spinning process that occurs in mild conditions of pressure and temperature, in aqueous solution and under optimised physicochemical conditions, so that minimal energy is required to form the thread. Spiders can spin different types of silks that exhibit various physical and biological features. Understanding the relationship between structure and function may soon lead to high performance and tailored materials and devices. Besides silk's performances and spinning process efficiency, silk proteins (spidroins) may become a renewable and biodegradable source of materials that exhibit attractive biocompatibility properties. Considering striking recent scientific advances, spider silk inspired materials maybe beneficial to humans and help to reduce the ecological footprint of societies. Nevertheless, designing truly green and efficient functional materials is complex, and much remains to be carried out to reach this objective. Producing spider silk inspired materials at industrial scale also raises fundamental sustainability questions, including those related to the supply of the raw material, the appropriateness of using spidroins and broader issues related to technology, economics and governance. This paper first summarises the characteristics of natural silk that may lead to innovative applications and may facilitate green technologies. Then, some challenges are presented in a context where societies urgently need to reduce the environmental impact of their activities. Finally, we address global sustainability challenges for spider inspired silk and material engineering.